The impact of podoconiosis, lymphatic filariasis, and leprosy on disability and mental well-being: A systematic review. - Oumer Ali; Asrat Mengiste; Maya Semrau; Abraham Tesfaye; Abebaw Fekadu; Gail Davey (PLoS Neglected Tropical Diseases)
Leprosy, podoconiosis, and lymphatic filariasis (LF) are among the priority neglected tropical diseases (NTDs) in Ethiopia. The disability, psychosocial, and mental health status of people affected by these NTDs are still overlooked in global NTD discourse. The objective of this systematic review was to synthesize the existing evidence describing the disability, psychosocial, and mental health status of people affected by leprosy, podoconiosis, and LF prior to developing a holistic physical and psychosocial care package for these individuals. We searched papers reporting on disability, psychosocial, and mental health status linked to these 3 NTDs. The protocol was registered in PROSPERO with registration number CRD42019128400. Peer-reviewed articles were searched and extracted from Medline, PsycINFO, Global Health, and Embase. Articles published in English, irrespective of the year of publication, using a quantitative study methodology, were included. Abstracts and full texts were reviewed by 2 reviewers. Data were extracted and narratively summarized, as the studies were heterogeneous and used different outcome measures. Out of 1,318 titles/abstracts screened and 59 full text studies reviewed, 24 fulfilled the inclusion criteria. Fourteen studies provided evidence of the disability associated with leprosy, podoconiosis, or LF. Ten studies provided evidence on the association between the 3 NTDs and mental health or psychosocial outcomes. The prevalence of grade 2 disability varied from 3.9% to 86%. The most commonly reported mental health impacts were depression and mental distress. A high burden of mental illness was reported, varying from 12.6% to 71.7%; the suicidal ideation was also high (18.5%). In conclusion, disability and poor psychosocial and mental health status are associated with leprosy, podoconiosis, and LF. For optimum management of these NTDs, holistic care including both physical and psychosocial interventions is vital.